What governs the success of aquaculture field schools - Insights from Odisha and Chattisgarh - Saha, G S; De, H K; Mahapatra, A S; Panda, N (Journal of the Inland Fisheries Society of India, 2021)
ICAR-CIFA piloted four Aquaculture Field Schools (AFS), a model of the farmer to farmer extension, of which three are in Odisha and one in Chhattisgarh. The AFSs are attracting farmers and stakeholders as they provide a platform to share experience and cross-learning. In this research, an attempt has been made to identify the factors that contribute to the successful performance of AFS. Data were collected from 166 user farmers selected randomly from the list available with operators. Five variables viz., age of fish farmer, frequency of visit to AFS, duration of visit, interaction with the fellow farmers, advocation of advanced technologies of ICAR-CIFA to other farmers were observed to be significantly contributing to yield of fish. The multiple correlation coefficient indicated that there was a significant and positive correlation between the observed and predicted value of fish yield (p<0.05). Key words Aquaculture Field schools; Fish farmer; Factors